História, mito e identidade em O Conquistador, de Almeida Faria. - Lima, Silvani Lopes (2006)
This Mastership Dissertation uses as corpus analysis the novel O Conquistador by Almeida Faria. The work interpretation considers three reading points: History, Mith, and Identity. First, we make a survey of the Sebastianism instauration historical context in Portugal, because the dialog established into the work proposes a review of these historical references, made possible by the use of irony, intertext, and periodic reversion. We still search to define sebastianism through the Claude Lévi Strauss thought who says that a myth can be reused for ends of historical legitimation, and through the Roland Barthes conception of myth as a linguistic phenomenon, ideologically set. The reflection about identity is from Eduardo Lourenço s idea that there would be a hyperidentity problem in Portugal. This situation is seen as a result of a country attachment to the heroic past, in part imagined. Besides, the Walter Benjamin s formulations about the archaic narrator clarify the villager s universe where the novel s main character was born and grew up. These individual subject characteristics, who experiences a conflict between reason and imagination, point to a collective subject representation. The novel, that presents a first-person narrator, holds, through the main character Sebastião de Castro, an awkward point with the Portuguese king D. Sebastião. The periodic reversion game processed into the work causes laughter and produces the myth and history demythification.